Hybrid Reinforcement of Asphalt-Concrete Mixtures Using Glass and Polypropylene Fibers - Abtahi, Sayyed Mahdi; Esfandiarpour, Saman; Kunt, Mehmet; Hejazi, Sayyed Mahdi; Ebrahimi, Milad Ghorban (Sage Publications Ltd, 2013)
There is a constant effort to improve the performance of asphalt-concrete (AC) mixtures. Among various modifiers for asphalt, fibers have received much attention for their improving effects. This paper introduces the novel concept of hybrid reinforcement of AC mixtures using polypropylene (PP) and glass fibers. Individually, glass fiber reinforced AC and PP fiber modified AC mixtures have exhibited superior performance compared to other fiber reinforced samples. Therefore, in this work, these two types of fibers were used simultaneously to improve the performance of the AC mixtures. This type of hybrid AC composite can be engineered by taking advantage of the tacky property of PP fiber around its melting point and the high modulus of glass fiber. In this way, PP fibers with the length of 12 mm were blended with bitumen at different percentages. Glass fibers with the length of 12 mm were also added to aggregates. Marshall and Specific Gravity tests were performed on hybrid reinforced asphalt-concrete (HRAC) samples by taking advantage of a Superpave Gyratory Compactor. In the case of the bituminous specimens, penetration, softening point and ductility tests were carried out. The results revealed that PP fibers decrease penetration and ductility of modified bitumen, while the softening point value is increased compared to unmodified bitumen specimen. Marshall Test results illustrate that PP can statistically affect the properties and improve the consistency of the mixture. Using a combination of 0.1% of glass fiber plus 6% of PP presented the best hybrid reinforcement through increasing stability and decreasing flow. Therefore, it is concluded that this novel HRAC is suitable for use in hot regions due to growth in the void total mix (VTM) and stability.
Keywords: Polypropylene (PP) fiber; Glass fiber; Asphalt-Concrete; Marshall Stability; Hybrid Reinforcement